2001
DOI: 10.1364/josaa.18.000442
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-cavity surface-emitting resonances in photonic crystal films

Abstract: It is shown that thin films of dielectric, etched through with a suitably chosen lattice of holes, can support surface-emitting vertical resonances with very-high-cavity Q factors (approximately 10(5) in the case of Al(x)GaAs(1-x) on oxidized AlyGaAs1-y). A Bloch-wave expansion is used to develop a complete vector-field analysis of these resonances and to reveal their underlying physics. Since they do not require multilayer mirrors, such resonators are a practical and simple replacement for conventional vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…First, the characterization of the photonic band structure, or dispersion relation (k), was carried out using an angularly resolved transmission and reflection surface coupling technique. [42][43][44][45]35,22,16,46 In this technique the 1D PhC is used to couple incident light into the resonant modes. The periodicity of the dielectric here provides the necessary in-plane wave vector enhancement via a reciprocal lattice vector G. That is, in the plane of the PhC:…”
Section: Sample and Setupsmentioning
confidence: 99%
“…First, the characterization of the photonic band structure, or dispersion relation (k), was carried out using an angularly resolved transmission and reflection surface coupling technique. [42][43][44][45]35,22,16,46 In this technique the 1D PhC is used to couple incident light into the resonant modes. The periodicity of the dielectric here provides the necessary in-plane wave vector enhancement via a reciprocal lattice vector G. That is, in the plane of the PhC:…”
Section: Sample and Setupsmentioning
confidence: 99%
“…The EFS are labelled s or p by considering whether the mode is excited as either s or p at °=0 ϕ . In the case of the 1D GaN PhC the EFS describe ellipses deformed near the X point, whereas in the case of the 2D GaN PhC, the EFS are more complex [27][28][29][30][31][32][34] The curves show the results of the numerical calculations, which are found to be in excellent agreementIn-Plane Wavevector (cm -…”
mentioning
confidence: 62%
“…The EFS are obtained by the intersection of the dispersion surfaces and the horizontal plane associated with a constant value ofω . [27][28][29][30][31][32][33][34] Cowan and Young 18 have studied theoretically the SHG produced by coupling of both the fundamental and the SH fields into resonant Bloch modes. They concluded that by optimising the photonic structure, enhancement by up to six orders of magnitude may be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…8 -10 to recover them. Studies have shown that the field associated to guided waves in a multilayer 6 or to guided Bloch waves in a MBG, 16 can be very important as compared to that of the continuum spectrum. Hence, the emitter may couple to them preferentially.…”
Section: Highly Directive Light Sources Using Two-dimensional Photonimentioning
confidence: 99%